The impact of doctrine and concepts on the development of the Serbian Armed Forces capabilities - Ostojić Miroslav M.; Karavidić Zoran M.; Projović Damir M. (Војно дело, 2017)
The strategic doctrinal field of the defense system is of particular importance for the reform and further development of the Serbian Armed Forces. In this field, the security environment is analyzed, the missions, objectives and tasks of the elements of the defense system are set and the preparation, organization, use and protection of the Serbian Armed Forces are defined. The military is a large and complex organizational system that has a sensitive role in the society and the state function in certain political, normative, legal, spatial, temporal, educational and other conditions that at the same time represent the framework of the military doctrine and the environment in which it can be used. The adoption of laws and strategic doctrinal documents, which define the security environment, set the missions, objectives and tasks of the elements of the defense system, is very important for the organizational-functional part and its effectiveness and efficiency in countering contemporary challenges, risks and threats. This response requires the necessary skills and specific knowledge of the military activity on how to use these skills.